The state of erythropoiesis in piglets under the influence of iron and germanium nanoparticles - Kovalchuk, O.; Tomchuk, V.; Danchuk, V.; Karpovsky, V. (Scientific Progress & Innovations, 2024)
The relevance of the conducted research is due to the lack of information in the available literature regarding the impact of iron and germanium nanoparticles on the state of erythropoiesis in piglets. The aim of the study was to determine the effect of administering iron and germanium nanoparticles to sows on the number of erythrocytes, hemoglobin content, and hematocrit index in their piglets. The experiment was conducted on 24 sows of the large white breed, aged 2–3 years, divided into two groups (control and experimental). The sows in the experimental group were given a complex of iron nanoparticle compounds (3 mg/day) and germanium (0.01 mg/day) for ten days, starting ten days before farrowing. Blood samples from five piglets born to the sows in the experimental group were taken on the second, seventh, and twenty-first days of life. The effect of postnatal adaptation on the number of erythrocytes in the blood of piglets during the experiment was F = 534.6 > FU = 4.49 (P<0.001), hemoglobin content was F = 55.5 > FU = 4.49 (P<0.001), and hematocrit index was F = 11.1 > FU = 4.49 (P<0.004). A significant effect of administering iron and germanium nanoparticles to sows on the number of erythrocytes in the blood was found (F = 11.7 > FU = 4.49; P<0.004). Administering iron and germanium nanoparticles to sows had a significant effect on the number of erythrocytes (ղ²ᵪ = 0.74; P<0.01), hemoglobin content (ղ²ᵪ = 0.83; P<0.001), and hematocrit index (ղ²ᵪ = 0.75; P<0.01) in the blood of 2-day-old piglets. When sows were given iron and germanium nanoparticles for ten days before farrowing, the number of erythrocytes in the blood of their 2-day-old piglets was 12.8% higher (P<0.001), hemoglobin content was 14.3 % higher (P<0.001), and hematocrit index was 14.5 % higher (P<0.05) compared to the control group. Thus, iron and germanium nanoparticles may play an important role in improving erythropoiesis in piglets. Prospects for further research consist in the development of modern methods of increasing the productivity and resistance of sows with the help of metal nanoparticles.